Design : Liège 2008 - Biennale internationale. (Liège : Office Provincial des Métiers d'Art Liège, 2008)
Levivier, Geneviève ; Atelier Ariane Lespire ; Atelier Blink ; Atelier Fenestra ; Bataille, Thierry ; Beguin, Marie ; Lecler, Christophe ; Biasiolo, Giovanni ; Bihain, Michaël ; Boonen, Anne Mie ; Burm, Rudy ; Charles, Raphaël ; Charlier, Louise ; deFaet Studio ; De Ponti, Matthijs ; Gorissen, Paul ; De Rudder, Nora ; De Vree, Marc ; Druez, Luc ; Fettweis, Baudouin ; Garzaniti, Mario ; Guillaume, Lionel ; Fabry, Amandine ; Marichal, France ; Herbecq, Bernard ; Humier, Laurence ; Huygelen, Els ; Zoete, Dirk ; Fanny-Sun K ; Knapic, Aurore ; Marquet, Isabelle ; Meert, Hugo ; Mertens, Marleen ; Parisse, Jean-François ; Rauw, Thomas ; Schanzer, Sem ; Smits, Romy ; Studio Peyman Design ; Tambour, Dani ; Van Praet, Frans ; Vartic, Véronica ; Velasti, Claude ; Vondenhoff, Monique ; Welter, Alix ; Wynants, Dirk ; Koch, Pascal ; Richard, Frédéric ; Dagonnier, Ronald ; Abdelhamid, Rashid ; Regis-R ; Sellner, Theodor ; Artschwager, Richard ; Elst, Jan Vander ; Hermans, Linde ; Devriendt, Jos ; Willenz, Sylvain ; Carrigan, James ; El-Asmar, Nedda ; Michaux, Henriette ; Peeters, Monique ; Beuys, Joseph ; Doléac, Florence
contactgegevens per designer
Frans
Exhibition. DDDDR (Domestic Design in der Deutschen Demokratischen Republik) meets Joseph Beuys. Exhibition. Design Liège 2008 : Biennale internationale. Liège. Musée de l'Art wallon de la Ville de Liège. Stad Luik. Le Centre Pro Chemnitz. Office Provincial des Métiers d'Art Liège. 26.09.2008 - 19.10.2008
boek